A 2009 Social Accounting Matrix (SAM) for South Africa - Davies, Rob; Thurlow, James (International Food Policy Research Institute, 2013)
This paper documents a South African Social Accounting Matrix (SAM) for the year 2009. The national SAM is built using official supply-use tables, national accounts, state budgets, and balance of payments, and so provides a detailed representation of the South African economy. It separates 49 activities and 85 commodities; labor is disaggregated by education level; and households by per capita expenditure deciles. Information on labor is drawn from the 2009 Quarterly Labor Force Survey and on households from the 2005 Income and Expenditure Survey. Finally, the SAM identifies government, investment and foreign accounts. It is therefore an ideal database for conducting economywide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.